Mathematics Learning for Slow Learners at Regular Schools - Woro Anglia Banda Sutomo; Tatang Herman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Slow learners or also known as slow learners have unique characteristics. One of them is that slow learners have low memory and concentration. Mathematics teachers’ understanding of slow learners in regular schools needs to be considered so that slow learners achieve the same goals as regular students in learning mathematics. In general, this study aims to describe and analyze how the process of learning mathematics in slow learners in regular schools. This study uses a qualitative approach. Data collection techniques using interviews. The main data used in this study is primary data. The data in this study are the results of unstructured interviews with the required informants. Based on the results of the analysis obtained (1) the importance of teachers and parents in overcoming problems in slow learners, (2) the strategy or approach used by the teacher is one of the supporting factors for the success of slow learners in the mathematics learning process, (3) teachers in regular schools have several obstacles in the mathematics learning process such as not being too familiar with implementing inclusive education in regular schools, (4) regular schools recommending the parents of the students concerned to transfer slow learners to inclusive schools so that slow learners get more special attention in learning, especially mathematics learning